1999
DOI: 10.1038/13776
|View full text |Cite
|
Sign up to set email alerts
|

The fusion gene Cbfb-MYH11 blocks myeloid differentiation and predisposes mice to acute myelomonocytic leukaemia

Abstract: T he heterodimeric CBF transcription factor genes (CBFA2 (also known as AML1) and CBFB) are the most common translocation targets in human acute myeloid leukaemia (AML), accounting for 30% of AML cases 1 . Approximately onehalf are attributable to a chromosome 16 inversion, inv(16)(p13; q22), found con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
230
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(244 citation statements)
references
References 15 publications
12
230
0
2
Order By: Relevance
“…It may be a common underlying mechanism for the pathogenesis in AML1-associated leukemia. However, recently generated transgenic or knock-in mice showed that AML1 mutations are critical for the development of AML, but that one or more additional mutations are necessary for leukemogenesis [10][11][12]. This accepted hypothesis is supported by the cytogenetic findings in the case of our patient exhibiting a complex karyotype.…”
supporting
confidence: 70%
“…It may be a common underlying mechanism for the pathogenesis in AML1-associated leukemia. However, recently generated transgenic or knock-in mice showed that AML1 mutations are critical for the development of AML, but that one or more additional mutations are necessary for leukemogenesis [10][11][12]. This accepted hypothesis is supported by the cytogenetic findings in the case of our patient exhibiting a complex karyotype.…”
supporting
confidence: 70%
“…CBFb-SMMHC prevents the development of de®nitive hematopoiesis during murine embryogenesis and obviates the formation of lymphoid and myeloid cells in adult mice (Castilla et al, 1996(Castilla et al, , 1999. The ability of CBFb-SMMHC to inhibit cell cycle progression might account for these phenotypes (Cao et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, 84% of CBFb þ /CBFbÀMYH11 chimeras (Castilla et al, 1999), which do not develop leukaemia in their first year of life, died from AML FAB M4 (that is myelomonocytic variant)-type disease when administered a single dose of ENU 2-6 months after treatment. In contrast, none of the wild-type chimeras treated with ENU developed disease, concluding that CBFb-MYH11 blocks differentiation, but cooperation with further oncogenes is necessary for leukaemogenesis.…”
Section: Knock-in Modelsmentioning
confidence: 99%